SHM_121163_HST_3D Ceramic Mug - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a ceramic mug from the Middle Ages. This mug was collected from Slottsfjärden in Kalmar, Sweden and is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=656

Link to Sök I Samlingarna

https://samlingar.shm.se/object/EDD894CD-FCEA-495A-9812-81F24DE02563
Keywords: Museum Object; 3D Model; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Kalmar; Dynamic Collections; Slottsfjärden; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi